Interface effects on the effective behavior of some Kelvin-Voigt viscoelastic heterogeneous bodies - C. Licht (2018)
© 2014 IOS Press and the authors. All rights reserved. The effective behavior of a solid made from a periodic distribution of inclusions in a matrix is investigated. Inclusions and matrix are linearly elastic or viscoelastic of Kelvin-Voigt type (and possibly rigid for the inclusions) while the link between them can be pure adhesion or viscous friction with bilateral contact or involve a very thin viscoelastic layer. As long as one constituent is viscoelastic, the effective behavior is no longer of Kelvin-Voigt type but with memory.